2020
DOI: 10.1371/journal.pone.0239492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pooled sample analysis strategy in expediting case detection in areas with emerging outbreaks of COVID-19: A pilot study

Abstract: Timely diagnosis of COVID-19 infected individuals and their prompt isolation are essential for controlling the transmission of SARS-CoV-2. Though quantitative reverse transcriptase PCR (qRT-PCR) is the method of choice for COVID-19 diagnostics, the resource-intensive and time-consuming nature of the technique impairs its wide applicability in resource-constrained settings and calls for novel strategies to meet the ever-growing demand for more testing. In this context, a pooled sample testing strategy was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…[ 17 ] shows a similar result for pools of size 30. In addition, several other studies find no loss of sensitivity for smaller pools, e.g., [ 18 20 ] use pool sizes of 5, 8, and 10, respectively. Not surprisingly [ 21 , 22 ], show that the dilution effect is more pronounced when the infected specimens in the pool have low viral loads; the window period analysis in [ 21 ] indicates that the low viral load typically occurs for specimens that are collected either too early or too late after infection.…”
Section: Introductionmentioning
confidence: 88%
“…[ 17 ] shows a similar result for pools of size 30. In addition, several other studies find no loss of sensitivity for smaller pools, e.g., [ 18 20 ] use pool sizes of 5, 8, and 10, respectively. Not surprisingly [ 21 , 22 ], show that the dilution effect is more pronounced when the infected specimens in the pool have low viral loads; the window period analysis in [ 21 ] indicates that the low viral load typically occurs for specimens that are collected either too early or too late after infection.…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, the NPVs of pooled testing are initially lower than those of individual testing, but they quickly increase and become higher than those of individual testing ( Figure 2G) when the prevalence rate under pooled testing is significantly lower than that under individual testing ( Figure 2B). However, research that assumes a fixed prevalence shows that pooled testing always leads to lower NPVs than those of individual testing 21 . Test sensitivity and specificity affect epidemic dynamics differently under different testing strategies, as shown in Figure 5.…”
Section: Flexible Testing Strategy the Objective Of Testing During Amentioning
confidence: 99%
“…Cumulative data since early in the epidemic have suggested that a window of about a week or two, starting 1-2 days before symptoms, a period associated to high viremia in the airways, is responsible for much of the transmission (He 2020). A major deterrent to surveillance is the fact that asymptomatic individuals, along with pre symptomatic cases, are responsible for many infections (reviewed by Huff & Singh, 2020). Association of transmission to higher viremia levels (La Scola 2020, Larremore 2020) suggests that even tests less sensible than the current real-time PCR (rt-qPCR) tests may be useful to curb transmission.…”
Section: Introductionmentioning
confidence: 99%
“…We introduced a voluntary throat wash plus saliva collection, offered to asymptomatic individuals from different areas of the institute, and tested the feasibility of using samples pooling (Abdalhamid 2020, Singh 2020, Yelin 2020) to minimize reagents and equipment use.…”
Section: Introductionmentioning
confidence: 99%